2020
DOI: 10.3390/ijms21051849
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Placental Amino Acid Transporter Expression and mTORC1 Signaling Activity Contributes to Fetal Growth Retardation in Diabetic Rats

Abstract: Alterations in placental transport may contribute to abnormal fetal intrauterine growth in pregnancies complicated by diabetes, but it is not clear whether the placental amino acid transport system is altered in diabetic pregnancies. We therefore studied the changes in the expressions of placental amino acid transporters in a rat model of diabetes induced by streptozotocin, and tested the effects of hyperglycemia on trophoblast amino acid transporter in vitro. Our results showed that the expressions for key is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Thus, it has been shown that tumour growth during pregnancy can alter the regulation of pathways responsible for amino acid transport through the placenta, which occurs through the activation of p38 MAPK signalling [25,26]. In addition, mTORC1 regulates placental amino acid transport by modulating the isoforms of the system A and system L transporters on the surface of trophoblasts [27,28]. Based on the changes in metabolites observed, the tumour growth during pregnancy was able to decrease the availability of nutrients or alter placental cell activity, leading to foetal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that tumour growth during pregnancy can alter the regulation of pathways responsible for amino acid transport through the placenta, which occurs through the activation of p38 MAPK signalling [25,26]. In addition, mTORC1 regulates placental amino acid transport by modulating the isoforms of the system A and system L transporters on the surface of trophoblasts [27,28]. Based on the changes in metabolites observed, the tumour growth during pregnancy was able to decrease the availability of nutrients or alter placental cell activity, leading to foetal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differentially expressed tsRNAs in normal-size and IUGR porcine skeletal muscle were mainly enriched in metabolic pathways, Rap1 signaling pathway, endocytosis, mTOR signaling pathway, and AMPK signaling pathway. It is known that energy metabolism and endocrine abnormalities are the main factors leading to IUGR ( Sharma et al, 2017 ), and the mTOR signaling pathway has been considered the core signaling pathway involved in IUGR ( Xu et al, 2020 ). In addition, signaling pathways and biological processes enriched with differentially expressed tsRNAs and highly expressed tsRNAs highly overlapped.…”
Section: Discussionmentioning
confidence: 99%
“…The placental IR pathway is altered by hyperinsulinism and activates the downstream endothelial carbon monoxide synthase to stimulate increased placental angiogenesis[ 45 ], thereby affecting placental nutrient metabolism. Animal and in vitro experiments have shown that amino acid transport proteins are downregulated in offspring with growth restriction, and the activity of placental mTORC1 is reduced in STZ-induced GDM rat models, resulting in a decrease in L-system amino acid transport proteins in the placenta, which is associated with intrauterine growth restriction and a reduced birth weight[ 46 ]. It has also been found in human and in vitro experiments that IL-15 is upregulated in the placenta of GDM patients and promotes trophoblast proliferation in vitro through the JAK/STAT signaling pathway, which is negatively correlated with neonatal weight[ 47 ].…”
Section: Impacts Of Gdm On Placental Transport Functionmentioning
confidence: 99%